Estimasi Perhitungan Kebutuhan Daya Kapal dengan Menggunakan Matlab - Hutauruk, Ronald Mangasi; Rengi, Pareng (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
The power requirement of ship must comply its form and principle dimension to make efficient fishing operational cost. To estimate power requirement of a ship conducted by vary approach such as Guldhamer Methods. Manual calculation by using this methods somewhat sophisticated and not practical since can only be done by certain people. Thus, to make it more simple, all the patterns are modified to be Matlab Graphical User Interface. The result shows that scoop netter power is 25,0754 HP calculated by using Matlab Application, meanwhile in the real condition the magnitude of fisher fishing vessel is 26 HP. There was discrepancy approximately about 4% where it was caused by measurement calculation in the field. Thus, this application can be used as a reference in calculation power requirement of a fishing vessel.